Food street and hotel survival: an exploratory study from netizen perspective during pandemic Covid-19 - Ruzulan, Zulaipa; Jamaludin, Mohammad Aizat; Hashim, Khairusy Syakirin Has-Yun (Skopje : International Balkan university, 2022)
Pandemic COVID-19 has affected many industries including the hospitality industry where hotel operators are among the most affected due to the movement restriction order (MCO) authorized by the government. Since this industry highly relies upon the local and foreign visitors, this phenomenon simultaneously made the number of visitors shrink drastically and consequently affects the hotel business like employee retrenchment and many hotels closed down. Owing to this, the hotels need to find out short term alternative to survive during this emergency time by selling their food on the street since their lodging service is affected most because of very low demand by the clients. Indeed, survival is crucial to sustaining the hotel business especially to safeguard the employees’ welfare due to the difficulty to find a new job if the employee is terminated during this hard time. Thus, this paper is going to explore the perception of netizens on the efforts done by the hotel in selling their food on the street during this pandemic era. An exploratory study will be adopted for this study where the response and reaction of the netizens to the news published via social media will be analyzed. This study would expect that the netizen provides positive and negative reactions to the alternative made by the hotel operators because of food street vendors' competitions, the image of the hotel, hygiene and the quality of the food as well as pricing. This study would benefit the government and the hotel operators in ensuring the sustainability of the hotel business and the living standard of the local community.